2012
DOI: 10.3892/etm.2012.502
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of miR-155 and miR-146a expression levels in formalin-fixed/paraffin-embedded tissue of patients with diffuse large B-cell lymphoma

Abstract: Abstract. It has been found that aberrant expression of microRNAs (miRNAs) is strongly associated with carcinogenesis. In the present study, we investigated the expression of miR-155 and miR-146a in diffuse large B-cell lymphoma (DLBCL) patients (n=90). The expression levels of miR-155 and miR-146a were significantly higher in de novo DLBCL patients. miR-146a expression levels were associated with miR-155, lactate dehydrogenase, β 2 microglobulin, c-myc, International Prognostic Index status and Eastern Cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…Aberrant expression of miR-146a was correlated with complete remission rate, higher overall response rate and longer progression-free survival time in patients with diffuse large B-cell lymphoma (Zhong et al 2012). In this study, the tissue levels of miR19b and miR-146a significantly influenced the OS in NSCLC patients with TNM stages I, II and III.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Aberrant expression of miR-146a was correlated with complete remission rate, higher overall response rate and longer progression-free survival time in patients with diffuse large B-cell lymphoma (Zhong et al 2012). In this study, the tissue levels of miR19b and miR-146a significantly influenced the OS in NSCLC patients with TNM stages I, II and III.…”
Section: Discussionmentioning
confidence: 69%
“…Overexpression of miR-146a can also inhibit NF-κB activity, thereby inhibiting proliferation and invasion of cancer cells as well as inducing apoptosis (Paik et al 2011;Li et al 2012a;Chen et al 2013a). However, miR-146a is upregulated in diffuse large B-cell lymphoma (Zhong et al 2012) and some invasive human breast cancer cell lines . Li et al (2012b) reported that miR-146a was highly expressed in brain metastasis in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies had elucidated an increased level of miR-155 expression in aggressive activated B-cell-like (ABC) subtype of DLBCL, primary mediastinal Bcell lymphoma (PMBL) and CLL. Their mean fold-change values had spanned from 3 to 19 in patients with DLBCL [29][30][31][32][33][34][35][36][37]. As well, a lot of studies have found down regulation of miR-155 expression levels within BL versus CLL, MCL and FL [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that, compared with normal controls, miR-155 is significantly upregulated in DLBCL, and that its expression is significantly increased in patients with non-GCB-type versus GCB-type DLBCL (20). The central role of miR-155 in the pathogenesis and aggressiveness of DLBCL has been clearly defined (9): miR-155 directly downregulates V-Myc avian myelocytomatosis viral oncogene homolog (MYC) antagonists, including mitotic arrest deficient-like 1, MYC-associated factor X (MAX)-interacting protein 1, and MAX network transcriptional repressor.…”
Section: Functions and Targets Of Dysregulated Mirs In Dlbclmentioning
confidence: 99%